Multi-generational adaptation to Solanum nigrum increases reproduction and decreases microbial diversity of Aphis gossypii - Wang, Peng; Jing, Yu-Xi; Ma, Ya-Jie; Wang, Dan; Shan, Yong-Pan; Hu, Hongyan; Wu, Changcai; Song, Xian-Peng; Ren, Xiangliang; Ma, Yan; Ma, Xiaoyan (Frontiers in Sustainable Food Systems, 2025)
Aphis gossypii Glover (Hemiptera: Aphididae) causes considerable damage to crop yields globally. Solanum nigrum (Solanales: Solanaceae), an annual malignant weed, serves as a crucial weed host for A. gossypii. However, the potential mechanisms by which A. gossypii adapts to different hosts during the transition between crops, such as Gossypium hirsutum (Malvales: Malvaceae) and S. nigrum remain elusive. We calculated the life table parameters of A. gossypii after rearing on S. nigrum for ten generations. The fifth generation of A. gossypii (T5) exhibited the strongest adaptability to S. nigrum, demonstrating notably higher values of r (intrinsic rate of increase), λ (finite rate of increase), and fecundity compared to the first generation of A. gossypii (T1). Upon retransferring T1, T5, and the tenth generation of A. gossypii (T10) were retransferred to G. hirsutum (designated as T1-M, T5-M, and T10-M, respectively), the T5-M showed superior r, λ, and fecundity compared to both T1-M and T10-M. 16S rRNA sequencing and qPCR analyses indicated a significant decrease in the diversity of the symbiotic bacterial community in both T5 and T10. Notably, Buchnera and Arsenophonus were two dominant symbiotic bacteria related to metabolism and host adaptability in A. gossypii. The relative abundance of Buchnera in T5 and T10 significantly increased compared to M and T, while the relative abundance of Arsenophonus decreased markedly. KEGG (Kyoto Encyclopedia of Genes and Genomes) function prediction analysis suggested that the roles of symbiotic bacteria in A. gossypii are primarily linked to metabolic processes. Therefore, the adaptation of A. gossypii to S. nigrum enhances its population expansion on G. hirsutum, potentially involving the metabolic functions of Buchnera and Arsenophonus. These findings provide a theoretical foundation for the scientific management of A. gossypii and S. nigrum in the fields.